The Implementation of Safe Learning Environments in Early Childhood Education - Syamsiyati, Rosida Nur; Makruf, Imam; Purnomo, SF Luthfie Arguby (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
A safe learning environment in early childhood education is an important aspect in supporting children's optimal development. This research was conducted to find out and analyze how early childhood education institutions have implemented a safe learning environment. This research used a qualitative approach with a case study method conducted from August to November 2024. The subject of this research is the class teacher, while the informants are the principal, accompanying teachers, and parents of MTA Bulu Kindergarten. The data collection methods used were observation, interview, and documentation. The validity of the research data, researchers used method and source triangulation techniques. The results showed that MTA Bulu Kindergarten has implemented several programs to create a safe learning environment. Some of the strategies that have been carried out include ensuring the safety of child-friendly buildings, compiling SOPs, making class agreements, implementing positive discipline, conducting regular safety talks and emergency drill activities, ensuring the availability of first aid facilities, implementing anti-violence policies, conducting bullying assessments, involving parents and related stakeholders, and forming violence prevention and handling teams.